Comparative study on effects of pH, electrolytes, and humic acid on the stability of acetic and polyacrylic acid coated magnetite nanoparticles. (April 2023) - Liu, Juanjuan; Zhao, Juntao; Louie, Stacey M.; Gao, Xubo; Zhang, Ping; Liang, Dongli; Hu, Yandi
Abstract: The poor colloidal stability of magnetite nanoparticles (MNPs) limits their mobility and application, so various organic coatings (OCs) were applied to MNPs. Here, a comparative study on the colloidal stability of MNPs coated with acetic (HAc) and polyacrylic acids (PAA) was conducted under varied pH (5.0–9.0) in the presence of different concentrations of cations and anions, as well as humic acid (HA). Comparing the effects of various cations and anions, the stability of both HAc/PAA-MNPs followed the order: Na +  > Ca 2+ and PO4 3−  > SO4 2−  > Cl −, which could be explained by their adsorption behaviors onto HAc/PAA-MNPs and the resulting surface charge changes. Under all conditions even with more anion adsorption onto HAc-MNPs (0.14–22.56 mg/g) than onto PAA-MNPs (0.04–18.34 mg/g), PAA-MNPs were more negatively charged than HAc-MNPs, as PAA has a lower pHIEP (2.6 ± 0.1) than that of HAc (3.7 ± 0.1). Neither the HAc nor PAA coatings were displaced by phosphate even at considerably high phosphate concentration. Compared with HAc-MNPs, the stability of PAA-MNPs was greatly improved under all studied conditions, which could be due to both stronger electrostatic and additional steric repulsion forces among PAA-MNPs. Besides, under all conditions, Derjaguin-Landau-Verwey-Overbeek (DLVO) explained well the aggregation kinetic of HAc-MNPs; while extended DLVO (EDLVO) successfully predict that of PAA-MNPs, indicating steric forces among PAA-MNPs. The aggregation of HAc/PAA-MNPs was all inhibited in varied electrolyte solutions by HA (2 mg C/L) addition. This study suggested that carboxyl coatings with higher molecular weights and p K a values could stabilize MNPs better due to stronger electrostatic and additional steric repulsion. However, in the presence of HA, these two forces were mainly controlled by adsorbed HA instead of the organic pre-coatings on MNPs. Graphical abstract: Image 1 Highlights: OC-MNPs aggregated faster in Ca 2+ than in Na  +  by stronger charge neutralization. Anion adsorption onto HAc-MNPs were higher than that onto PAA-MNPs. Electrostatic and van der Waals forces controlled the stability of HAc-MNPs. PAA stabilized MNPs more than HAc due to stronger electrostatic and steric forces. The stabilities of HAc/PAA-MNPs were similar after humic acid adsorption.